The Asymptotic Behaviour of the Solutions of a Degenerate Reaction-diffusion Problem (Journal of Partial Differential Equations, 1994)
Consider in this paper the existence, uniqueness and asymptotic behaviour of the solutions of the mixed problem for a class of degenerate quasilincar parabolic equations and properties of the corresponding stationary solutions.